Exploring manual therapy in the management of irritable bowel syndrome in adults: A scoping review - Natalia Płóciennik-Korycka; Sara Maria Pani; Bogumiła Bruc; Paolo Contu; Magdalena Wrzesińska (Complementary Therapies in Medicine)
Introduction: IBS is a prevalent gut-brain interaction disorder characterized by abdominal pain and altered bowel habits, significantly affecting quality of life (QoL). IBS contributes to substantial work absenteeism and economic burdens and often coexists with other somatic and psychiatric conditions, with psychological well-being being a critical determinant of QoL. IBS sufferers often turn to MT due to dissatisfaction with conventional treatments. However, no comprehensive review has assessed the evidence for MT in treating IBS. Objective: The objective of this review is to identify and map the available evidence on the effects of various manual therapy (MT) techniques on the biopsychosocial functioning, well-being, and QoL of individuals with irritable bowel syndrome (IBS). Methods: A comprehensive search was conducted in PubMed, Embase, and Scopus. Studies involving adults with IBS and investigating the effects of MT on biological, psychological, and social outcomes, well-being, or QoL were included. A scoping review was conducted following PRISMA-ScR guidelines. Study quality was assessed using The National Heart, Lung and Blood Institute (NHLBI) Study Quality Assessment Tools. The protocol for this review was registered with the Open Science Framework and is available at https://doi.org/10.17605/OSF.IO/QN4WU. Results: Of 730 records identified, 30 studies met the inclusion criteria (9 trials, 21 reviews). The interventions reviewed included osteopathic manipulative treatment (OMT), acupuncture, acupressure, reflexology, traditional Chinese spinal orthopaedic manipulation, and Tuina. The most frequently assessed outcomes were biological and psychological variables, as well as QoL, with well-being being the least commonly examined. Conclusions: Although the results suggest potential benefits of MT in IBS treatment, they should be interpreted with caution due to the lack of robust trials, inconsistent findings, and occasional adverse events. High-quality randomized controlled trials and standardized outcome measures are necessary to validate these therapies and improve IBS management.